1651. In vitro synergy test and clinical outcome of antibiotics combination regimens for carbapenem-resistant Acinetobacter baumannii. (15th December 2022) - Baek, Jin Yang; Kim, Hyemee; Kang, Yu Ri; Kang, Sujeong; Huh, Hee Jae; Lee, Nam Yong; Ko, Jae-Hoon; Cho, Sun Young; Kang, Cheol-In; Chung, Doo-Ryeon; Peck, Kyong Ran; Huh, Kyungmin
Abstract: Background: Acinetobacter baumannii is one of the leading etiologic agents of serious hospital-acquired infections. A. baumannii is characterized by a high rate of carbapenem resistance, which often leads to treatment failure and poor outcome. Combination regimens of antibiotics are often used, but their clinical benefit and optimal target are yet unclear. Methods: We selected carbapenem-resistant A. baumannii (CRA) isolates from the patients who received antimicrobial treatment for bloodstream infection (2012–2018) or pneumonia (2019–2020) and survived for ≥5 days. In vitro synergy was tested using checkerboard method and time-kill assay for colistin (COL) and tigecycline (TGC) with the following antibiotics: meropenem (MRO), ampicillin/sulbactam (A/S), minocycline (MIN), ciprofloxacin (CIP), and with each other. Clinical information was collected to compare the patient outcome between those who were treated with combination regimens with in vitro synergy and those who were not. Results: A total of 72 isolates were selected. When combined with colistin, MRO showed the highest rate of synergy (20.8%), followed by A/S (16.7%), and MIN (13.9%). No antibiotics showed synergy with TGC in >10% of the tested isolates. Most isolates with positive checkerboard test also tested positive with time-kill assay for COL (97.6%), but not for TGC (20.0%). Among 57 patients with monobacterial infection caused by the tested CRA isolates, nine (15.8%) received combination regimens with in vitro synergy. All patients received colistin, and carbapenem was the companion antibiotic in all patients in the synergistic combination group. There was no significant difference in all-cause 30-day mortality (55.6% vs 33.3%, p=0.266), treatment response, and microbiologic response. Multivariable analysis also demonstrated no significant difference in mortality by synergistic combination regimen (adjusted odds ratio, 4.59; 95% confidence interval, 0.73–33.88). Conclusion: Checkerboard method showed an excellent concordance with time-kill assay for COL-based combinations, but not with TGC-based regimens. However, combination regimens with a proven in vitro synergy were not associated with better outcomes. Disclosures: All Authors : No reported disclosures.